Why the Germans? Why the Jews? : envy, race hatred, and the prehistory of the Holocaust - Aly, Götz, 1947- (Metropolitan Books, Henry Holt and Company, 2014)
"A provocative and insightful analysis that sheds new light on one of the most puzzling and historically unsettling conundrums Why the Germans? Why the Jews? Countless historians have grappled with these questions, but few have come up with answers as original and insightful as those of maverick German historian Götz Aly. Tracing the prehistory of the Holocaust from the 1800s to the Nazis' assumption of power in 1933, Aly shows that German anti-Semitism was--to a previously overlooked extent--driven in large part by material concerns, not racist ideology or religious animosity. As Germany made its way through the upheaval of the Industrial Revolution, the difficulties of the lethargic, economically backward German majority stood in marked contrast to the social and economic success of the agile Jewish minority. This success aroused envy and fear among the Gentile population, creating fertile ground for murderous Nazi politics.Surprisingly, and controversially, Aly shows that the roots of the Holocaust are deeply intertwined with German efforts to create greater social equality. Redistributing wealth from the well-off to the less fortunate was in many respects a laudable goal, particularly at a time when many lived in poverty. But as the notion of material equality took over the public imagination, the skilled, well-educated Jewish population came to be seen as having more than its fair share. Aly's account of this fatal social dynamic opens up a new vantage point on the greatest crime in history and is sure to prompt heated debate for years to come"--